The lived experiences of women on intimate partner violence in a Victim Support Centre in Tshwane, South Africa - Mpja, Nonhlanhla Precious (My University, 2021)
Intimate Partner Violence (IPV) is widespread all over the world. It is a major problem in the Western and developing countries, which apply different regulations to curb and tackle the problem. In Sub-Saharan Africa, this is prevalent in rural and urban areas. In South Africa, IPV is a common occurrence and is widespread, resulting in physical, mental and emotional scars not only on the women who experience it, but also on their families and communities. The aim of this study was to explore the lived experiences of women exposed to IPV at Re-bafenyi Victim Support Centre in order to understand how violence has impacted their lives. The study identified factors that lead to IPV by men against their partners. Further, intervention strategies that are most effective in empowering victims were examined. Purposive sampling was used to select 10 women aged between 18 and 59 years old who were survivors of IPV and were sheltered at Re-bafenyi Victim Support Centre. Semi-structured interviews were carried out to collect data. The findings of the study indicate that participants were adversely affected by physical violence, emotional violence, controlling behavior and sexual violence. The factors which contributed to the violence ranged from excessive conflict, male dominance in the household, men in multiple relationships with other women, alcohol and drug abuse, cohabitation and financial difficulties. The main conclusion drawn from the study was that IPV leaves permanent wounds with the women who experienced it, and the healing process get prolonged when there is no proactive response. The recommendations include the need for proactive responses in dealing with intimate partner violence cases by organisations rendering victim support services to avoid secondary victimization
A research report submitted to the School of Human and Community Development, Faculty of Humanities, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirement for the Master of Arts in the field of Social Development